2018
DOI: 10.1021/acs.jchemed.8b00384
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Globalization and Successful Adaptation Strategies in Implementing a “Scientific Writing and Authoring” Course in China

Abstract: This paper describes the adaptation of an upper-division undergraduate seminar course taught at the University of Missouri in Columbia (MU) to the Summer School Program of the University of Chinese Academy of Sciences in Beijing (UCAS). The course "Scientific Writing in Chemistry" addresses an essential need for science students across the globe to receive experiential education in scientific writing. An assignment-based curriculum was developed to instruct students on best practices in writing a scientific pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…For example, Wei and Li [ 10 ] found that college students’ learning adaptability mainly includes five aspects: learning motivation, learning ability, environmental factors, teaching mode and learning attitude. Yang et al [ 13 ] also pointed out that the main factors of college students’ learning adaptation include learning motivation, teaching mode, learning ability, learning attitude and environmental factors. Li et al [ 16 ] found that there existed adjustment to Chinese culture and mental health issues among foreign students on Chinese university campuses during the COVID-19 pandemic from a collaborative ethnographic study perspective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Wei and Li [ 10 ] found that college students’ learning adaptability mainly includes five aspects: learning motivation, learning ability, environmental factors, teaching mode and learning attitude. Yang et al [ 13 ] also pointed out that the main factors of college students’ learning adaptation include learning motivation, teaching mode, learning ability, learning attitude and environmental factors. Li et al [ 16 ] found that there existed adjustment to Chinese culture and mental health issues among foreign students on Chinese university campuses during the COVID-19 pandemic from a collaborative ethnographic study perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al [ 11 ] conducted an open questionnaire survey of experts, teachers, and students, used the two dimensions of learning motivation and learning behaviour, and constructed the structure and components of college students’ learning adaptability through eight factors: self-management, method application, professional interest, pressure regulation, hell-seeking tendency, information utilisation, environmental choice and knowledge transformation [ 12 ]. Yang et al [ 13 ] conducted a study of 918 college students from four different universities and performed exploratory factor analysis and confirmatory factor analysis on the survey data. The results showed that the main factors of college students’ learning adaptation include learning motivation, teaching mode, learning ability, learning attitude and environmental factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation